Day-by-Day Blood Pressure Variability Is Associated With Neurological Functional Outcome After Acute Ischemic Stroke - Yang, Changqiang; Liu, Kai; Song, Yue; Gong, Shenzhen; Ye, Runyu; Zhang, Zhipeng; Chen, Xiaoping (Frontiers in Neurology, 2020)
Background Previous studies on the association between blood pressure variability in the acute ischemic stroke and functional outcome have yielded inconsistent results. We aimed to investigate the impact of day-by-day blood pressure variability within 7 days of onset on functional outcome at 3 months after acute ischemic stroke. Methods Total 367 patients hospitalized for ischemic stroke within 48 hours of onset were enrolled. The acute stage of ischemic stroke was defined as the time period from symptom onset to 7 days. During this period, blood pressure was measured twice daily. Day-by-day blood pressure variability, including standard deviation (SD) and coefficient variation (CV) were derived and compared to functional outcome. We dichotomized function outcome according to mRS score and unfavorable outcome was defined as mRS≥3. Results The patients with unfavorable outcome had significantly higher systolic BPV (within 7 days of onset) than those with favorable outcome (15.41±4.59 VS 13.42±3.95mmHg for SD, P＜0.001；11.54±3.23 VS 10.41±2.82 for CV, P=0.001). Multivariable logistic regression analysis revealed that systolic BPV was significantly and independently associated with the 3-month functional outcome (odds ratio[OR]=1.15, 95% confidence interval[CI]:1.07-1.22, P＜0.001 for SD; OR=1.15, 95%CI:1.06-1.26, P=0.001 for CV). In addition, After adjustment for multiple confounding factors, including age, gender, risk factors, stroke features, baseline severity, recanalized therapy, hemorrhagic transformation, pulmonary infection, white blood cell, estimated Glomerular Filtration Rate and mean BP, day-by-day BP variability was significantly correlated with an unfavorable outcome in the top versus bottom quartile of systolic BPV (OR=3.33, 95% CI:1.41–7.85, P=0.006 for SD; OR=2.27, 95%CI:1.04–4.94, P=0.037 for CV) during 3-month follow-up. Similar trends were also observed for diastolic BPV. More importantly, incorporating SD of systolic BP into the conventional prediction model could significantly increase the AUC for prediction of 3-month unfavorable outcome after acute ischemic stroke (0.84 VS 0.86; P=0.0416). Conclusions Increased day-by-day blood pressure variability of systolic or diastolic BP in the acute ischemic stroke was associated with higher risk for unfavorable outcome at 3 months independent of blood pressure levels. Combining SD of systolic BP with conventional risk factors could improve the prediction of unfavorable outcome.